Paradoxes of The Technogenic Society. On Nikolai Tverdynin’s Book Technics In the Literature of Different Countries and Periods: an Essay Monograph - V. S. Glagolev (Концепт: философия, религия, культура, 2020)
The review on the book of a former Emergency Ministry official and a philosophy professor Nikolai Mikhailovich Tverdynin published in 2020 in ANO Dialog Kul’tur publishing house analyses views on technology and technics that are manifested by acknowledged people across the globe. Two major beliefs are as follows: technophobic and technocratic. Dr. Tverdynin provides an unbiased description of their application to practice, as it becomes clear that technological threat awareness is a key feature of both attitudes. The book suggests that modern technical boom and its increasing involvement in education and personal development shall remain a vital, but not central method of acquiring new skills, as direct experience teaches not only to operate, but also to be a qualified worker and an individual even in sciences. Despite this and other opinion messages (remember the author’s past service), the book is not a journalist, but a scientific work, as it is void of ideology that accompanies technology. Overall, the book serves as an example of a rare accurate review of such an urgent issue and on such a thorough source collection.